Sarinah: Perkembangan Sebuah Pasar di Daerah Transmigrasi Rimbo Bujang (1977-2021) - Ika Ayu Novitasari; Zul Asri (Jurusan Sejarah FIS UNP, 2022)
This study examines the development of Sarinah Market in Rimbo Bujang District in 1977-2021. The research problems are formulated as follows: 1) How is the development of Sarinah Market in Rimbo Bujang from 1977 to 2021. 2) How is the existence of Sarinah Market on the economic dynamics of the Rimbo Bujang community. This study uses historical research methods consisting of four stages, namely heuristics, source criticism, interpretation, and historiography. The results of the study reveal that, first, the Sarinah Market has continued to develop from 1977-2021. The development of Sarinah Market can be seen from the development of traditional markets that provide all basic needs. Therefore, Sarinah Market is known as the traditional market of Rimbo Bujang which provides all the complete needs. In addition, market development is seen from market development, market management, market arrangement, types of merchandise, merchandise flows, and the market retribution system. Second, how is the existence of Sarinah Market on the economic dynamics of the Rimbo Bujang community. Keywords: Development, Sarinah Market Abstrak Penelitian ini mengkaji perkembangan Pasar Sarinah di Kecamatan Rimbo Bujang tahun 1977-2021. Permasalahan penelitian ini dirumuskan sebagai berikut: 1) Bagaimana perkembangan Pasar Sarinah di Rimbo Bujang 1977-2021. 2) Bagaimana keberadaan Pasar Sarinah terhadap dinamika ekonomi masyarakat Rimbo Bujang. Penelitian ini menggunakan metode penelitian sejarah yang terdiri dari empat tahapan yaitu heuristik, kritik sumber, interpretasi, dan historiografi. Hasil penelitian mengungkapkan bahwa, pertama, Pasar Sarinah terus mengalami perkembangan sejak tahun 1977-2021. Perkembangan Pasar Sarinah dapat dilihat dari adanya perkembangan pasar tradisional yang menyediakan segala kebutuhan pokok. Oleh karena itu, Pasar Sarinah dikenal sebagai pasar tradisional Rimbo Bujang yang menyediakan segala kebutuhan yang lengkap. Selain itu, perkembangan pasar dilihat dari pembangunan pasar, pengelolaan pasar, penataan pasar, jenis barang dagangan, arus barang dagangan, dan sistem retribusi pasar. Kedua, bagaimana keberadaan Pasar Sarinah terhadap dinamika ekonomi masyarakat Rimbo Bujang. Kata kunci: Perkembangan, Pasar Sarinah